2015
DOI: 10.3109/14397595.2015.1038425
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isokinetic and aerobic exercises on serum interleukin-6 and tumor necrosis factor alpha levels, pain, and functional activity in patients with knee osteoarthritis

Abstract: At the end of 6th week, there was no statistically significant decrease in serum pro-inflammatory cytokine levels in both the exercise groups, although C-reactive protein levels exhibited a strong trend toward significance. We found a significant decrease in visual analog scale and Western Ontario McMaster Osteoarthritis Index scores, and significant increase in functional capacity and muscle strength in both the exercise groups compared with those in the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…One study showed only the age range, which was from 41 to 63 years and 1 study included only those with a BMI <35 . One study included participants at risk of OA (i.e., no radiographic signs of OA, sedentary behavior, age >60 years, and a BMI >27) , and the remaining 11 studies included participants with or without pain but with radiographic knee OA, ranging from Kellgren/Lawrence (K/L) grades 1 to 4 (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study showed only the age range, which was from 41 to 63 years and 1 study included only those with a BMI <35 . One study included participants at risk of OA (i.e., no radiographic signs of OA, sedentary behavior, age >60 years, and a BMI >27) , and the remaining 11 studies included participants with or without pain but with radiographic knee OA, ranging from Kellgren/Lawrence (K/L) grades 1 to 4 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The types of exercise therapy interventions used were strengthening exercise in 5 studies , aerobic exercise in 3 studies , and a combination of strengthening and aerobic exercise in 5 studies (Table ). Biomarker samples were obtained at 4 to 24 weeks following the exercise therapy intervention in all the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Gomes et al 16 , aerobic exercise (walking training, three times/week for 12 weeks) was effective in decreasing the levels of soluble receptor for tumor necrosis factor (sTNFR2) from plasma, which has been associated with reduced inflammation in articular cartilage damage and improved physical function in OA patients 16 . Moreover, Samut et al 17 , found that aerobic exercise (walking training, 3 days/week for 6 weeks) decreased pain and increased functional capacity and muscle strength in patients with knee OA.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies showing that isokinetic muscle strengthening exercises improve proprioception, balance and physical function. [8][9][10][11][12][13][14] In this study, we aimed to assess the effect of quadriceps and hamstring strengthening on proprioception, balance, and physical function specifically in patients with Grade 2 or 3 knee OA, according to the Kellgren-Lawrence (KL) radiographic grading system and moderate risk of fall.…”
mentioning
confidence: 99%